PENERAPAN SISTEM PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) SEBAGAI PENGGERAK POMPA AIR PADA INSTALASI PENGOLAHAN AIR LIMBAH - Subandi, Subandi; Handiyanto, Muhammad Dimas Surya (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2022)
The need for poultry meat as public consumption from year to year is increasing, the price is relatively cheap and the commodity is continuously available. This has also led to an increase in the Chicken Slaughterhouse (RPA) industry. Wastewater from this chicken slaughterhouse has a high organic content so that it has the potential to pollute the environment, so we need a system for waste management. The Waste Water Treatment Plant (IPAL) functions to treat wastewater produced by community members. This IPAL uses a radial flow anaerobic system consisting of a rabic pro tank and an up flow filter tank. Water from sewage treatment can be directly channeled into rivers because it meets the quality standards of liquid waste. These IPAL treatment units consist of a control tank (screening), sedimentation tank, anaerobic reactor, aerobic reactor, final sedimentation tank and sludge drying bed sludge treatment which uses an electric pump to drain the waste to a filtration tank. This electric pump uses electrical power supply from the Solar Power Plant (PLTS) and PLN. The research results to be achieved are evaluating the utilization and performance of PLTS and planning a management model so that the IPAL can function optimally and sustainably.